2021
DOI: 10.1016/j.asmr.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Protocols for Superior Capsular Reconstruction Are Variable: A Systematic Review

Abstract: Purpose: To screen manuscripts that discuss rehabilitation protocols for patients who underwent superior capsular reconstruction (SCR) to elucidate whether a standard rehabilitation algorithm exists for SCR. Methods: A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta Analyses (i.e., PRISMA) guidelines. PubMed (MEDLINE) and Embase were searched using pertinent Boolean operation terms "superior capsular reconstruction" and "rotator cuff repair rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, a systematic review reported that many surgeons advocate starting strengthening or resuming activity between 6 and 12 weeks after SCR. 26 Thus, MRI should be performed before the initiation of strengthening exercises to ensure sufficient healing. Furthermore, postoperative serial MRI assessments need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review reported that many surgeons advocate starting strengthening or resuming activity between 6 and 12 weeks after SCR. 26 Thus, MRI should be performed before the initiation of strengthening exercises to ensure sufficient healing. Furthermore, postoperative serial MRI assessments need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%